Active Surveillance for Influenza Reduces but Does Not Eliminate Hospital Exposure to Patients With Influenza. (10th January 2017) - Coleman, Brenda L.; Ng, Wil; Mahesh, Vinaya; McGuire, Maja; Hassan, Kazi; Green, Karen; McNeil, Shelly; McGeer, Allison J.; Katz, Kevin
Abstract : OBJECTIVE: To describe the frequency, characteristics, and exposure associated with influenza in hospitalized patients in a Toronto hospital DESIGN/METHOD: Prospective data collected for consenting patients with laboratory-confirmed influenza and a retrospective review of infection control charts for roommates of cases over 3 influenza seasons RESULTS: Of the 661 patients with influenza (age range: 1 week–103 years), 557 were placed on additional precautions upon admission. Of 104 with symptoms detected after admission, 57 cases were community onset and 47 were nosocomial (10 nosocomial were part of outbreaks). A total of 78 cases were detected after admission exposing 143 roommates. Among roommates tested for influenza after exposure, no roommates of community-onset cases and 2 of 16 roommates of nosocomial cases were diagnosed with influenza. Of 637 influenza-infected patients, 25% and 57% met influenza-like illness definitions from the Public Health Agency of Canada (PHAC) and Centers for Disease Control and Prevention (CDC), respectively, and 70.3% met the Provincial Infectious Diseases Advisory Committee (PIDAC) febrile respiratory illness definition. Among the 56 patients with community-onset influenza detected after admission, only 13%, 23%, and 34%, met PHAC, CDC, and PIDAC classifications, respectively. CONCLUSIONS: In a setting with extensive screening and testing for influenza, 1 in 6 patients with influenza was not diagnosed until patients and healthcare workers had been exposed for >24 hours. Only 30% of patients with community-onset influenza detected after admission met the Ontario definition intended to identify cases, hampering efforts to prevent patient and healthcare worker exposures and reinforcing the need for prevention through vaccination. Infect Control Hosp Epidemiol 2017;38:387–392